Strategi Pembelajaran Guru Sekolah Minggu dalam Menghadapi Anak yang Pasif - Boni Boni; Yonatan Alex Arifianto; Reni Triposa (Sekolah Tinggi Teologi Kerusso Indonesia, 2023)
Sunday school teachers must be an example for every child. Sunday school teachers must also be able to provide exciting teachings and involve children in learning so that passive children can participate in learning. Using descriptive qualitative methods, this research can be concluded that. Teachers in Sunday schools can create effective teaching methods that involve children in teaching, such as the question-and-answer method, to encourage children to be active in the learning process, enabling them to be enthusiastic in the teaching process. Sunday school is essential in teaching, helping, and encouraging children to understand what the Bible provides as the right way to live in Christ. Children can shape their attitudes, behavior, and character by following God's commands through the Word of God, taught by parents and Sunday school teachers in the Christian faith. AbstrakGuru sekolah Minggu harus menjadi contoh untuk setiap anak juga harus bisa memberikan pengajaran yang menarik anak dalam pembelajaran. agar anak yang pasif bisa ikut serta dalam pembelajaran. Metode kualitatif dan deskritif untuk penelitian ini dapat disimpulkan bahwa. Guru di sekolah Minggu dapat menciptakan metode pendekatan yang efektif di sekolah Minggu yang melibatkan anak-anak dalam pendekatan seperti metode pengajaran tanya jawab untuk mendorong anak aktif dalam proses belajar yang mendorong mereka untuk semangat dalam proses pengajaran. Sekolah Minggu adalah peran penting dalam mengajar dan mendorong anak-anak untuk memahami Alkitab yang berikan sebagai cara hidup yang tepat di dalam Kristus.